MODEL FOR MAPPING EFFECT OF SPIRITUAL INTELLIGENCE ON HUMAN DECISION MAKING IN AMBIGUOUS ENVIRONMENT - I. Alam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Abstract. This Research paper analyses the impact of various human emotions on the strategic decision-making ability of an individual and proposes a framework establishing the relationship between 'Spiritual Intelligence and Decision Making'. It endeavours to connect the domain of 'human sciences' and 'computing', to propose a framework and an implementable AI-based model, wherein, the ambiguities of the environment and decision making has been modelled based on the fuzzy logic which captures an inherent uncertainty of emotions and stimulus. The framework can be applied for generating decisions based on the external and internal state of an individual. The reaction of an individual to a changing environment, manifesting in a mix of emotions is modelled. The model deals with five decision-making styles and four dimensions of spiritual intelligence. Further, the model has been validated by using statistical data collected through questionnaires from professionals working in the information technology industry. This paradigm gives a fuller picture towards an understanding of the human decision-making process through a computational model, while grounding the idea in the existing theory of human cognition.